The Contribution of Improvements in Irrigation Efficiency to Environmental Flows - Linstead, Conor (Frontiers in Environmental Science, 2018)
Increasing irrigation efficiency is often assumed to be a means of saving water and a route to increasing irrigated agricultural production or making water available for other purposes, such as communities, industry or ecosystems. There is a growing body of literature arguing that increasing irrigation efficiency does not reduce consumptive water use in agriculture, implying that no additional water is made available for supporting environmental flows. However, understanding the implications of changes in irrigation efficiency for environmental flows requires assessment at temporal and spatial scales between the daily to seasonal field level analysis of advocates for increasing irrigation efficiency to save water, and the annual basin scale view of some of its critics. When investigated at these intermediate temporal and spatial scales, there may be potential for improvements in irrigation efficiency to mitigate the effects of irrigation on flow timings to an ecologically meaningful extent. In situations where this is possible, in advance of implementing irrigation efficiency programmes, overall water consumption must be limited by an effective water allocation regime that explicitly recognises environmental flow needs in order to prevent expansion or intensification of irrigated agriculture. This paper sets out some of the key issues that practitioners working on environmental flows should consider in order to assess whether or not interventions to increase irrigation efficiency can support environmental flow objectives.